SEMINAR PENINGKATAN EKONOMI JEMAAT MELALUI BISNIS ONLINE DI PARSAHUTAON PGRI CISAUK, TANGERANG - Tolop Oloan Marbun (Jurnal PKM Setiadharma, 2023)
This article is a report on community service through a Seminar about increasing congregations’ economic through online business. The seminar was conducted for the members of Pasahutoan Gotorong Imanuel at Cisauk as the action of sharing ideas for the goodness of each member.  The community service was conducted through a seminar with discourse and discussion methods. The media was PowerPoint and TV Screens.  The purpose of this report is reference for increasing the congregation’s economy through online business. The method is qualitative research with a literature study. It started by collecting literature such as a recent journal. The analytic method is content analysis. Analytic results display descriptive. The result is the seminar has impacted the member to start and continue their online business.